Correction: Andreadis et al. The Advent of a New Era in Digital Healthcare: A Role for 3D Printing Technologies in Drug Manufacturing? Pharmaceutics 2022, 14, 609 - Ioannis I. Andreadis; Christos I. Gioumouxouzis; Georgios K. Eleftheriadis; Dimitrios G. Fatouros (MDPI AG, 2022)
In the original publication [...]